Psychological Stressors and Coping Experiences in Indian Classical Dancers - Kavya Jain; Ashwini Govinda (Journal of Dance Medicine & Science, 2026)
Introduction: Indian classical dance (ICD) is a popular and highly structured art form that encompasses mime, choreographed movements, and rhythmic footwork along with traditionally influenced cultural practices which affect the overall psychological health of dancers. Although it is known that dance enhances emotional well-being, the literature investigating the mental health of ICD practitioners (ie, resilience, challenges, and coping) is scarce. This research studies how ICD influences dancers’ emotional well-being and resilience, the mental health challenges they face, and the coping mechanisms they use. It also examines various cultural and training practices which shape the above factors. Methods: Guided by an interpretivist paradigm and inspired by the Biopsychosocial Model and Resilience Theory, this qualitative study used semi-structured interviews to gather in-depth narratives from 12 Indian classical dancers aged 18 and above. Participants were from different ICD styles identified through purposive sampling. Interviews were audio-recorded, transcribed, and analyzed using Braun and Clarke’s reflexive thematic analysis. Results: Dancers described ICD as enhancing their emotional expression and regulation, inner balance, and resilience through disciplined practices and a continuous cycle of practice and performance. But they also described serious mental health challenges, including pressure to perform and be perfect, power battles for control and inadequate support in balancing dance with other aspects of their lives. Cultural expectations and practice of devotional acts provided both support and added pressure. Participants used a range of coping mechanisms, such as expressive movement, spiritual engagement, community and teacher support, reflective practices, and personal regulatory strategies. Conclusions: ICD works as a system that affects the dancers in a dual manner, as its rigorous training and cultural expectations can cause psychological and physical stress, but its expressive, spiritual, and community-supporting aspects serve as significant tools for emotional regulation, resilience, and emotional well-being.